You are on page 1of 7

# Different kinds of Mathematical Induction

Given

A N,

[1A

(aA a+1A)]

A = N.

## (2) (First) Principle of Mathematical Induction

Let P(x) be a proposition (open sentence), if we put
A = {x : x N
If

## (2) P(k) is true for some k N P(k+1) is true

then
P(n) is true n N.
(3) Second Principle of Mathematical Induction
If

## (1) P(1) is true;

(2) 1 i k, P(i) is true

## [i.e. P(1) P(2) . P(k) is true]

P(k+1) is true
then

P(n) is true n N.

If

(2) P(k-1) P(k)

then

is true;
is true for some

## k N\{1} P(k+1) is true

P(n) is true n N.

If

(2) P(k)

then

## is true for some

is true;

k N P(k+m) is true

P(n) is true n N.

If

(2) P(k)

then

is true;

## is true for some

k N P(k+2) is true

P(n) is true n N.

Page

## More difficult types of Mathematical Induction

(7) Backward M.I.

If

kN

## (2) P(k) is true for some

then

P(k1) is true

P(n) is true n N.

If

## (1) P(1) is true;

k N P(2k+1) is true;

kN

## (3) P(k) is true for some

then

P(k1) is true

P(n) is true n N.

If

k N, where k a

then

P(k+1) is true

If

k N Q(k) is true

## (2) P(k) is true for some

k N P(k+1) is true

then

## (11) Double M.I.

Double M.I. involves a proposition P(m, n) with two variables m, n.

If

is true m, n N;

## (2) P(m+1, n) and P(m, n+1) are true for some

P(m+1, n+1) is true
then

P(m, n)

is true m, n N.
Page

m, n N

p n < 22 .
n

## Prove that the nth prime number

Solution

p n < 22 .
n

Let

P(n)

be the proposition :

For

P(1),

p1 = 2 < 2 2

Assume

P(i)

is true

P(1)

is true.

## p1 < 2 2 , p 2 < 2 2 ,..., p k < 2 2 . (*)

1

s.t. 1 i k , i.e.

1

For

P(k + 1),

1

## For any prime factor

Since p1, p2 , ., pk

p k +1 p < 2 2

of

k +1

Let

{an}

P(k + 1)

< 22

k +1

p < 22

k +1

is true.
P(n)

is true n

n-1

an = 2

Prove that

## By the Second Principle of Mathematical Induction,

Recurrive formula

k +1

a1 = 2, a2 = 3

## and an+2 = 3an+1 2an .

+1.

Solution
Let

P(n)

For

P(1) P(2),

Assume
i.e.

be the proposition :

a1 = 2 = 21-1 + 1,

ak = 2k-1 + 1
ak+1 = 2 + 1
P(k+2),

a2 = 2 = 22-1 + 1 .

k

For

an = 2n-1 + 1 .

(1)

(2)

is true.

## By the Second Principle of Mathematical Induction,

Odd Even Mathematical Induction
Let

a1 = 2,

Prove that

a2 = 2

an =

P(1) P(2)

## = 3ak+1 2ak = 3(2k + 1) 2(2k-1 + 1) = 2k+1 + 1

ak+2

P(k + 2)

an+2 = an + 1

1
(n + 1) + 1 1 + ( 1)n
2
4

].

Solution

Page

P(n)

is true n

is true.

## Let P(n) be the proposition :

an =

1
(n + 1) + 1 1 + ( 1)n
2
4

For P(1),

a1 = 1 =

1
(1 + 1) + 1 1 + ( 1)1
2
4

For P(2),

a2 =1 =

1
(2 + 1) + 1 1 + ( 1)2
2
4

Assume

].

i.e. a k =

## P(1) P(2) is true.

1
(k + 1) + 1 1 + ( 1)k
2
4

(*)

## For P(k + 2),

ak+2 = ak + 1 =
=

1
(k + 1) + 1 1 + ( 1)k + 1
2
4

1
[(k + 1) + 1] + 1 1 + ( 1)k +1
2
4

, by (*)

P(k + 2) is true.

P(n) is true n

## Backward Mathematical Induction

x + x2
Let f(x) be a convex function defined on [a, b], i.e. f ( x 1 ) + f ( x 2 ) 2f 1
for all x1, x2 [a, b].
2
For each positive integer n, consider the statement:
x + ... + x n
I(n) : If xi [a, b], i = 1, 2, , n, then f ( x 1 ) + ... + f ( x n ) nf 1
.

n
(a)

(b)

(c)

## (n 2) is true, then I(n-1) is true.

Solution
(a)

x + ... + x n
I(n) : If xi [a, b], i = 1, 2, , n, then f ( x 1 ) + ... + f ( x n ) nf 1

n
For I(21), since it is given that

Assume

I(2k)

x + x2
f ( x 1 ) + f ( x 2 ) 2f 1
.
2

I(21)

x 1 + ... + x 2 k
is true. i.e. f ( x 1 ) + ... + f ( x 2k ) 2 k f

2k

is true.

.(1)

For I(2k+1),
f ( x 1 ) + ... + f ( x 2k ) + f ( x 2k +1 ) + ... + f ( x 2k +1 )
x k + ... + x 2k +1
x + ... + x 2k x 2k +1 + ... + x 2k +1
x 1 + ... + x 2k
k
k 1
2k f
+ 2 f 2 +1 k
= 2 f
+ f
k
2
2
2k
2k

x 1 + ... + x 2k x 2k +1 + ... + x 2k +1
= 2 k f
+ f
2k
2k

x 1 + ... + x 2k + x 2k +1 + ... + x 2k +1
= 2 k +1 f
2 k +1

1 x 1 + ... + x 2k x 2k +1 + ... + x 2k +1
+
2 k 2 f
, by I(2)
2k
2k
2

Page

, by (1)

I(2k+1)

is true

(b)

## I(n) is true (n 2),

Assume
i.e.

x + ... + x n
f ( x 1 ) + ... + f ( x n ) nf 1

Put

xn =

x 1 + ... + x n 1
n 1

n 1 x 1 + ... + x n 1
+ n
= nf

n
n 1
n 1

, then

x + ... + x n 1
x 1 + ... + x n 1
f ( x 1 ) + ... + f ( x n 1 ) + f 1
nf

n 1
n 1
x + ... + x n 1
f ( x 1 ) + ... + f ( x n 1 ) ( n 1)f 1

n 1
(c)

n ,

(k

n = 2k r.

## Given a sequence {an}

(
(

)
)

2
S 2 m 1 = 2 m 4m 3m + 1

1
S 2 m = m 4m 2 + 3m + 1
2

S n = a i , prove that

Let

## a2m-1= 3m(m 1) + 1 and a2m = 3m2,

satisfying

i =1

where

....(1)
....(2)

Solution

Let

For

P(m)

be the proposition :

S2 m 1 =

Q(m)

be the proposition :

S2m =

S1 = a1 = 1

P(1),

Assume

P(k)

For

## Q(k), S2k = S2k-1 + a2k =

(b)

For

P(k + 1),
S2k+1 = S2k + a2k+1 =

Since

Since

1
m 4m 2 + 3m + 1
2

(1)

is true for

., i.e. S 2 k 1 =

(a)

1
m 4m 2 3m + 1
2

m=1.

1
k 4k 2 3k + 1
2

1
1
k 4k 2 3k + 1 + 3k 2 = k 4k 2 + 3k + 1 .
2
2

(*)

Q(k)

P(k + 1) is true.

is true.

1
k 4k 2 + 3k + 1 + [3(k + 1)k + 1]
2

[(

) (

1
4k 3 + 12k 2 + 12k + 4 3k 2 + 6k + 3 + (k + 1)
2

1
1
3
2
2
4(k + 1) 3(k + 1) + (k + 1) = (k + 1) 4(k + 1) 3(k + 1) + 1 .
2
2

(1)

P(1) is true.

(2)

P(k) is true

(1)

P(1) is true.

(2)

Q(k)

is true

Q(k)

Q(1)

is true

P(k + 1) is true

P(n) is true n

is true
P(k + 1) is true

Page

Q(k + 1) is true

Q(n) is true n

## Mathematical Induction with parameter

Let

, when a = 1
1
f(a, 1) =
.
0 , when a > 1, a N

and

f (a , n ) + 1
, when a = 1

f(a, n+1) =
.
f (a, n ) + f (a 1, n ) , when a > 1, a N

f (a , n ) =

Prove that

n (n 1)...(n a + 1)
a!

Solution

## Let P(n) be the proposition : f (a , n ) =

(1)

(2)

For

n (n 1)...(n a + 1)
a!

## When a = 1, L.H.S. = f(1, 1) = 1.

R.H.S. =

1
=1
1!

When a > 1,

L.H.S. = f(a, 1) = 0.

R.H.S. =

1(n 1)...(1 a + 1)
=0 .
a!

Assume

## is true for some

For

P(k)

., i.e.

When a > 1,

k (k 1)...(k a + 1)
a!

is true.

(2)

k
k +1
+1 = k +1 =
= R.H.S.
1!
1!

## L.H.S. = f(a,k) +f(a 1, k)

=

k (k 1)...(k a + 1) k (k 1)...(k a + 2)
+
, by (2), f(a,k) and f(a 1, k) hold .
(a 1) !
a!

k (k 1)...(k a + 2)
[(k a + 1) + a ]
a!

Comment

f (a , k ) =

P(1)

## When a = 1, L.H.S. = f(a, k + 1) = f(a, k) + 1 =

(1)

(k + 1)k (k 1)...(k a + 2)
a!

= R.H.S.

P(k + 1) is true.

## If the proposition with natural number

P(n) is true n

n contains a parameter

Page

## Double Mathematical Induction

Prove that the number of non-negative integral solution sets of the equation
x1 + x2 + + xm = n
is

f(m, n) =

m,n

(n + m 1) !
n !(m 1) !

(1)

Solution

Let P(m, n)
(a)

For
In

## be the given proposition.

P(1, n), The only non-negative integral solution set of the equation
(1) , f(1, n) =

(n + 1 1) ! = 1
n !(1 1) !

P(1, n) is true .

For

P(m, 1),

x1 = n is only itself .

## The non-negative integral solution sets of the equation

x1 + x2 + + xm = 1
are

In (1),

(b)

f(m, 1) =

P(m, 1)

Assume

(1 + m 1) ! = m
1!(m 1) !

is true .

m,n

. . i.e

## the number of non-negative integral solution sets of the equations :

are
For

x1 + x2 + + xm = n +1

(2)

x1 + x2 + + xm + xm+1 = n

(3)

f(m, n+1) =
P(m+1, n+1),

(n + m ) !
(n + 1) !(m 1) !

and

f(m+1, n) =

(n + m ) !

respectively .

n !m !

## The non-negative integral solution sets of the equation :

x1 + x2 + + xm + xm+1 = n + 1

(4)

## may be divided into two parts : xm+1 = 0 or xm+1 > 0 .

(i)

For

xm+1 = 0 , equation (4) becomes equation (2), and the number of non-negative integral solution
sets is

(ii)

For

f(m, n+1) =

(n + m ) !
(n + 1) !(m 1) !

## xm+1 > 0 , replace xm+1 by xm+1 + 1 and equation (4) becomes:

x1 + x2 + + xm + xm+1 = n , and the number of non-negative integral solution
sets is

f(m+1, n) =

(n + m ) !
n !m !

## The total number of non-negative integral solution sets is

(n + m ) ! + (n + m ) !
(n + 1) !(m 1) ! n !m !

(n + m ) ! [(n + 1) + m] = [(n + 1) + (m + 1) 1]
(n + 1) !m !
(n + 1) ![(m + 1) 1]!

Page

P(m, n)

is true m, n